2023
DOI: 10.3390/vaccines11020425
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neurological Complications after COVID-19 Vaccination: Report of the Clinical Scenarios and Review of the Literature

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), broke out in 2019 and became a pandemic in 2020. Since then, vaccines have been approved to prevent severe illness. However, vaccines are associated with the risk of neurological complications ranging from mild to severe. Severe complications such as vaccine-induced immune thrombotic thrombocytopenia (VITT) associated with acute ischaemic stroke have been reported as rare complications post-COVID-19 vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…These cases suggest that COVID-19 vaccination might be associated with the development of NMOSD in certain individuals, particularly those with a history of autoimmune or demyelinating disorders. A rare case of vaccine-associated herpes simplex encephalitis was reported by Chen et al [ 61 ] in a patient who received the Pfizer-BioNTech vaccine. This finding highlights the importance of considering the potential for atypical neurological complications following COVID-19 vaccination and underscores the need for further research to better understand the possible underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These cases suggest that COVID-19 vaccination might be associated with the development of NMOSD in certain individuals, particularly those with a history of autoimmune or demyelinating disorders. A rare case of vaccine-associated herpes simplex encephalitis was reported by Chen et al [ 61 ] in a patient who received the Pfizer-BioNTech vaccine. This finding highlights the importance of considering the potential for atypical neurological complications following COVID-19 vaccination and underscores the need for further research to better understand the possible underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sulaiman et al found that the use of thiamine as an adjunct therapy in critically ill patients with COVID-19 was associated with a lower incidence of thrombosis 364 . Chen et al successfully treated a patient with right facial weakness, after the second dose of the Moderna vaccine, with thiamine, riboflavin, and prednisolone 366 . Thus, postvaccination inflammatory mechanisms can thus also trigger neuropsychiatric symptoms via thiamine deficiency.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Except COVID-19 infection, COVID-19 vaccinations have been reported to induce severe neurological adverse effects, such as ADEM, cerebrovascular stroke, cerebral venous sinus thrombosis and encephalitis [9][10][11][12]. However, the neuropathological mechanism of COVID-19-associated ADEM or ADEM after COVID-19 vaccinations is still not clear [4,13]. Similarly, the case presentation is a patient with SARS-CoV-2 infection presenting stroke-like manifestations, such as right hemiparesis, hemiparesthesia and dysarthria.…”
Section: Introductionmentioning
confidence: 99%